Comparação da qualidade de leite de vacas em sistema de produção convencional e orgânico. - Santos, Florência Carneiro dos (2016)
The present work aimed at the physical-chemical analysis of milk produced in two systems, conventional and organic. Were made eight collections of the refrigeration tank of a property located in the municipality of Dois Vizinhos of a conventional system of production and 8 collections of the refrigeration tank of the Paranaense Center of Reference in Agroecology (CPRA) of organic production system, totaling 16 samples. The chemical composition variables that were compared were fat, protein, solids, deffated dry extract (ESD), and lactose. Somatic cell count (CCS) and total bacterial count (CBT) were performed in relation to microbiology and the tests foreseen in MAPA resolution 62. These analyzes were submitted to a 5% Tukey test comparing the averages obtained in each treatment. There was no significant statistical result for the variables fat, protein, solids, lactose, and ESD. However, conventional milk obtained higher CCS than organic milk.But, in contrast, the organic system presented CBT higher than the conventional system, both were above the limit established by IN 62.